The Volume of Nipple Aspirate Fluid Is Not Affected by 6 Months of Treatment with Soy Foods in Premenopausal Women(2) - Maskarinec, Gertraud (American Society for Nutrition, 2011)
Based on the hypothesis that soy food consumption may influence breast tissue activity, we examined its effect on the production of nipple aspirate fluid (NAF), a possible indicator of breast cancer risk. Of 310 premenopausal women screened, 112 (36%) produced at least 10 μL of NAF, the minimum for study participation. In a crossover design, we randomized 96 women to 2 groups who, in reverse order, consumed a high-soy diet with 2 soy servings/d (1 serving = 177 mL soy milk, 126 g tofu, or 23 g soy nuts) and a low-soy diet with <3 servings/wk of soy for 6 mo each separated by a 1-mo washout period. During each diet period, 3 NAF samples were obtained (baseline and 3 and 6 mo) using a FirstCyte Aspirator and 4 urine samples (baseline and 1, 3, and 6 mo) were analyzed for isoflavonoids by liquid chromatography tandem MS. Adherence to the study protocol according to 24-h dietary recalls and urinary isoflavonoid excretion was high. The drop-out rate was 15% (n = 14); 82 women completed the intervention. The 2 groups produced similar mean NAF volumes at baseline (P = 0.95) but differed in age and previous soy intake and in their response to the intervention (P = 0.03). In both groups, NAF volume decreased during the first 3 mo of the high-soy diet period and returned to baseline at 6 mo, but there was no effect of the high-soy diet on NAF volume (P = 0.50 for diet; P-interaction = 0.21 for diet with time). Contrary to an earlier report, soy foods in amounts consumed by Asians did not increase breast tissue activity as assessed by NAF volume.